(untitled) (American Journal of Islam and Society, 2010)
This short analytical book attempts to serve American decision-maker policy choices with respect to the “pivotal” country of Iran. The pivotal state thesis has sought to organize the United States’ national security strategy after the collapse of the Soviet Union and the end of the cold war.1Maloney applies it to the Iranian case, given that country’s geostrategic value and significant role in global issues and negotiations (pp. 4-5). She adopts the thesis’ main assumption that by investing attention and resources in regional heavyweights, the United States can benefit from the “multiplier” effect of their weight. Arguing that as the United States seeks to change its strategic approach toward the region, the author posits that focusing on the Muslim world’s pivotal states will help prioritize challenges and opportunities and thus better serve its vital interests (p. 5). She proceeds to do so by making the case for Iran’s crucial importance while outlining what she perceives to be its political, economic, security and theological dilemmas – presumably so that Washington and its allies can take advantage of them. The study also attempts to examine the shifts from reformist (Khatami) toward more radical (Ahmadinejad) politics in Iran’s domestic scene. She traces the reasons why the Iranian “reform movement,” under Khatami failed and attributes that outcome to self-imposed constraints (redlines), fear of bringing about instability, and the movement’s elitist structure (pp. 12- 13). Maloney also points to Ahmadinejad’s “perverse” but “compelling” incentive to preserve the long-standing antagonism toward the United States. She expresses her concern that such shifts may serve to undermine any remaining international consensus necessary to address “problematic elements of Iran’s foreign policy” (p. 23) ...